Study of controlling the content heavy metals Pb, Cu, Cd, and Cr in land using hyperaccumulator plants - Widyasari, Ni Luh; Rai, I Nyoman; Dharma, IGB Sila; Mahendra, Made Sudiana (Brawijaya University, 2024)
This study aimed to determine the types of hyperaccumulator plants that can absorb the heavy metal content of Pb, Cu, Cd, Cr based on the values of bioaccumulation factors (BAF) and translocation factors (TF). Results of the analysis showed that BAF value of the hanjuang plant (Cordyline fruicosa), for heavy metal Pb was 0.369; Cu 0.442; Cd 0.055; Cr 0.078 and TF value for heavy metal Pb 1.572; Cu 0.964; Cd 0.108; Cr 1.358. Croton plant (Codiaeum variegatum), had a BAF value of Pb 0.021; Cu 0.060; Cd 0.000; Cr 0.003 and TF value of Pb 3.638; Cu 0.000; Cd 0.000; Cr 1.399. Sansevieria plant (Sansevieria trifasciata) had a BAF value of Pb 0.090; Cu 0.036; Cd 0.015; Cr 0.002 and TF value of Pb 0.410; Cu 0.334; Cd 0.222; Cr 0.726. Sunflower plant (Helianthus annuus) had a BAF value of Pb 0.022; Cu 0.094; Cd 0.308; Cr 0.001 and TF value of Pb 1.930; Cu 0.399; Cd 1.383; Cr 1.361. Based on a comparison of BAF values, hanjuang plant was the best hyperaccumulator plant capable of accumulating Pb, Cu, Cr with a phytoextraction mechanism and accumulating Cd with a phytostabilization mechanism. At the same time, sunflower a hyperaccumulator plant with the best translocation factor where the roots of sunflower plants absorbed Pb, Cu, Cd, Cr, which were then translocated to the stems and leaves optimally through a phytoextraction mechanism.